Self-assembling peptide hydrogel for intervertebral disc tissue engineering. (December 2016) - Wan, Simon; Borland, Samantha; Richardson, Stephen M.; Merry, Catherine L.R.; Saiani, Alberto; Gough, Julie E.
Graphical abstract: Abstract: Cell-based therapies for regeneration of intervertebral discs are regarded to hold promise for degenerative disc disease treatment, a condition that is strongly linked to lower back pain. A de novo self-assembling peptide hydrogel (SAPH), chosen for its biocompatibility, tailorable properties and nanofibrous architecture, was investigated as a cell carrier and scaffold for nucleus pulposus (NP) tissue engineering. Oscillatory rheology determined that the system would likely be deliverable via minimally invasive procedure and mechanical properties could be optimised to match the stiffness of the native human NP. After three-dimensional culture of NP cells (NPCs) in the SAPH, upregulation of NP-specific genes ( KRT8, KRT18, FOXF1 ) confirmed that the system could restore the NP phenotype following de-differentiation during monolayer culture. Cell viability was high throughout culture whilst, similarly to NPCs in vivo, the viable cell population remained stable. Finally, the SAPH stimulated time-dependent increases in aggrecan and type II collagen deposition, two important NP extracellular matrix components. Results supported the hypothesis that the SAPH could be used as a cell delivery system and scaffold for the treatment of degenerative disc disease. Statement of Significance: Lower back pain (LBP) prevalence is widespread due to an aging population and the limited efficacy of current treatments. As LBP is strongly associated with intervertebral disc (IVD) degeneration, it is thought that cell-based therapies could alleviate LBP by repairing IVD tissue. Various natural and synthetic biomaterials have been investigated as potential IVD tissue engineering scaffolds. Self-assembling peptide hydrogels (SAPHs) combine advantages of both natural and synthetic biomaterials; for example they are biocompatible and have easily modifiable properties. The present study demonstrated that a de novo SAPH had comparable strength to the native tissue, was injectable, restored the IVD cell phenotype and stimulated deposition of appropriate matrix components. Results illustrated the promise of SAPHs as scaffolds for IVD tissue engineering.